231k views
0 votes
Answer to B pleaseeeeee???????

Answer to B pleaseeeeee???????-example-1
User Tjeerdhans
by
5.4k points

3 Answers

4 votes

Answer:

92

Explanation:

Substitute the given values for a and b into the expression

2a² + 5b²

= 2(- 6)² + 5(2)²

= (2 × 36) + (5 × 4)

= 72 + 20

= 92

User Tmp
by
5.6k points
2 votes

First you need to replace all of the letter A's with -6 and all of the B's with 2.

The equation would look like this

2(-6)^2+5(2)^2

Second, you solve what in is the parenthesis 2(-6)=-12 5(2)= 10

Third, you rewrite the problem. -12^2+10^2

Fourth, you need to figure out what the final answer would be.

-12^2=-144 and 10^2=100

The answer would be -144+100=-44

Sorry!!! This is probably Wrong, I didn't use an algebra calculator or anything to check the answer. I didn't remember if I needed to bring the number in parenthesis to the power before or after multiplying.

User Kunal Tanwar
by
5.5k points
2 votes

Answer:

if i did my math right then the answer is 244

Explanation:

User FourtyTwo
by
5.0k points